Polypropylene blends and composite: Processing-morphology-performance relationship of injected pieces - Constanino, Maria Alejandra (2020)
Polypropylene (PP) is a low-cost plastic commodity, which currently is in a transition zone between massive use and engineering applications due mainly to its limited mechanical properties, such as low tensile and impact resistance. That is the reason why PP is usually modified with additives and particles to improve its mechanical and thermal performance and thus meet the requirements demanded by engineering applications. Besides, PP composites are suitable materials to be processed by a simple, fast, automatic, and massive technique such as injection molding. This makes PP composites attractive for several applications. However, it is important to keep in mind that PP composites’ performance depends not only on their intrinsic properties but also on processing conditions. This chapter will summarize the relationship between processing and performance of several PP composite—micro, nano, and hybrid—injected parts with the aim of generating a bridge between technologic knowledge and scientist knowledge.